PEMBELAJARAN MENULIS PUISI DENGAN MENGGUNAKAN MEDIA PODCAST UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK KELAS VIII SMPN 2 MARGAHAYU BANDUNG TAHUN PELAJARAN 2022/2023 - Titin Nurhayatin; Helawati, Ela; Supian, Supian (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
This research is motivated by the difficulties and disinterest of students in writing poetry texts. This is because students do not understand the techniques in writing poetry texts. In addition, students are still not trained in developing their creative thinking in writing poetry texts. To overcome this problem, the authors chose podcast learning media to improve students' ability to write poetry texts and students' creative thinking skills in class VIII SMPN 2 Margahayu. The problem in this study is related to the low ability of students in writing poetry texts and the ability to think creatively. This study aims to examine the effectiveness of podcast media and its impact on the ability to write poetry texts and increase creative thinking skills. The ability of class VIII students of SMPN 2 Margahayu in writing poetry texts is in good category. In addition, the ability to think creatively is also in another good category. Based on the results of statistical calculations, it can be obtained that podcast media has an impact on the ability to write poetry texts and the ability to think creatively. This is supported by statistical calculations. There are significant differences in writing poetry texts and students' creative thinking in the experimental class using podcast media and the control class using image media. This study uses a mix method with data collection techniques through tests, observations, and interviews. Based on the results of the research, it can be concluded that learning to write poetry texts has an impact on students' creative thinking abilities. In addition, it can be an alternative to choosing a learning model in class. It is evident from the results of the pretest writing poetry texts that the average experimental class student obtained 57.69, while the average posttest score for the experimental class obtained 81.92 which indicates an increase in value. Likewise, the average score of students' creative thinking pretest is 63.5, while the posttest average score is 77.66, also showing an increase Keywords: Creative thinking, Podcast, Write, Poetry.